2020
DOI: 10.3390/su13010185
|View full text |Cite
|
Sign up to set email alerts
|

Pulses for Healthy and Sustainable Food Systems: The Effect of Origin on Market Price

Abstract: Pulses are widely acknowledged for their high nutritional value due to high protein content, low content in calories, and low glycemic index; they are a good alternative to animal proteins thus offering a considerable number of social, environmental, and health benefits. Despite pulses being widely acknowledged as healthy and sustainable food, in mainly European countries, consumption is growing but still lower than the recommended level, production is unprofitable in comparison to the current market prices le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
3
8
0
Order By: Relevance
“…However, this interest is not reflected in the analysis of the hedonic price from which it emerges as only one Apulian producer (i.e., Cerealitalia) has presented on the label the indication of the geographical origin of the legumes used. Despite this lack of interest from companies, the literature appears to be in agreement with our result, showing how this attribute is already relevant for different types of products: plant-based beef meatballs [49], wine [21], sea urchins [52], oil [53] and legumes [54]. Depending on the social and cultural changes that have taken place, the needs and preferences expressed by consumers have changed, passing from the satisfaction of subjective needs and those related to the health of the individual, to ethical and environmental needs, paying attention to the community.…”
Section: Interpretation and Comparison Of The Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, this interest is not reflected in the analysis of the hedonic price from which it emerges as only one Apulian producer (i.e., Cerealitalia) has presented on the label the indication of the geographical origin of the legumes used. Despite this lack of interest from companies, the literature appears to be in agreement with our result, showing how this attribute is already relevant for different types of products: plant-based beef meatballs [49], wine [21], sea urchins [52], oil [53] and legumes [54]. Depending on the social and cultural changes that have taken place, the needs and preferences expressed by consumers have changed, passing from the satisfaction of subjective needs and those related to the health of the individual, to ethical and environmental needs, paying attention to the community.…”
Section: Interpretation and Comparison Of The Resultssupporting
confidence: 89%
“…This means that the launch of innovative and healthful products such a legume-based snack necessitates a campaign of promotion and communication through labelling, which are considered as an indispensable source of information for the consumer and, very often, the main tool by which the latter can evaluate the attributes of the product that they would not otherwise be able to maximize, such as its purchase utility and the product’s perceived quality [ 52 ]. On the one hand, these analyses have been widely applied to different products, such as lentils as such [ 54 ], processed tomatoes [ 68 ], ultra high temperature milk [ 27 ] and the yogurt market [ 26 ], but on the other hand, not yet enough attention has been paid to legume snacks, which are considered to be an innovative food that have been increasingly widespread in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, [ 31 ] analyzed the marginal prices associated with different countries of origin in the Chinese dairy market. [ 32 ] evaluated the effects on prices of the declaration of origin of food products considering a group of European countries. Overall, these studies found evidence that the declaration of origin would have positive effects on milk or food prices.…”
Section: Introductionmentioning
confidence: 99%
“…They boost productivity by facilitating nitrogen fixation [21][22][23] and help reduce dependence on cereal monoculture, thereby contributing to climate change mitigation and biodiversity preservation [24][25][26][27]. They also exhibit lower water and nutritional requirements, along with greater potential for environmental adaptability [28]. Specifically with regards to biodiversity, lentils stand out among all legumes due to their significant genetic variability and regional specialization, particularly in Italy.…”
Section: Introductionmentioning
confidence: 99%